La grande festa e i Movimenti religiosi, una prospettiva materialista nell’antropologia religiosa - Pino Schirripa (AM. Rivista della Società Italiana di Antropologia Medica, 2023)
The Great Feast and The Religion of the Oppressed, a Materialist Perspective in the Anthropology of ReligionsThe text analyses Lanternari’s two volumes published in 1959 and 1960. After situating the theoretical perspective of the Italian scholar in the context of the tradition of studies tracing back to Pettazzoni, it illustrates the intense relationship he had with Ernesto de Martino, whose influence is evident in the two volumes. The analysis of the two texts aims to show how Lanternari participated in an original way in the renewal of Italian anthropology. This is evident both for the new analytical perspective that emerges in La grande festa, and for the theme of millenarianism, at the centre of the volume on religious movements, seen in its anti-colonial function. This is certainly a new theme in the Italian context. The thesis is that, through the two volumes and especially the first, Lanternari has constructed a religious anthropology of a materialist stance. This becomes explicit, even in the words of the author, with the re-edition of La grande festa in 1976.La grande festa e i Movimenti religiosi, una prospettiva materialista nell’antropologia religiosaIl testo analizza i due volumi di Lanternari usciti nel 1959 e 1960. Dopo aver inquadrato la prospettiva teorica dello studioso italiano nel contesto della tradizione di studi che risale a Pettazzoni, si illustra l’intenso rapporto che egli ebbe con Ernesto de Martino, la cui influenza nei due volumi è evidente. L’analisi dei due testi vuole evidenziare come Lanternari partecipi in modo originale al rinnovamento dell’antropologia italiana. La cosa è evidente sia per la nuova prospettiva analitica che emerge ne La grande festa, sia per il tema dei millenarismi, al centro del volume sui movimenti religiosi, vista nella sua funzione anticoloniale. Tema sicuramente nuovo nel panorama italiano. La tesi è che, attraverso i due volumi e soprattutto il primo, Lanternari abbia costruito una antropologia religiosa di stampo materialista. Cosa che diventa esplicita, anche nelle parole dell’Autore, con la riedizione de La grande festa del 1976.